Enhanced biomethanation of palm oil mill effluent during anaerobic treatment in a closed digester tank - Sulaiman, Alawi (2010)
The methane capture project from anaerobic treatment of palm oil mill effluent(POME) treatment for clean development mechanism (CDM) is becoming increasingly important due to the problems caused by the utilisation of fossil fuels such as global warming, air and water pollution, resource depletion, high energy price, acid rain and others. The traditional way of treating POME using large open ponds or tanks system is an unsustainable practice because large amounts of methane are released to the atmosphere contributing to the greenhouse gas (GHG) emission. By closing the digester, methane could be captured and utilized to generate electricity for internal consumption or Tenaga Nasional Berhad (TNB) grid connection. Moreover, with CDM registration with the United Nation Framework Convention on Climate Change (UNFCCC), the captured methane could be converted into carbon credit and could be traded in the international market as certified emission reduction (CER). Hence, there is an urgent requirement for the industry to capture as much methane as possible so that higher CER and electricity power could be generated to partly finance the overall project cost. For this purpose there is an urgent need to understand the various operational conditions that contribute to the improved methane production in terms of methane yield and productivity without affecting the organic removal efficiency such as accelerated start-up process, effect of higher sludge recycling rate, effect of mixing and effect of co-digestion. In chapter 4, the accelerated start-up process of the closed digester tank (CDT) was achieved by transfer the seed sludge from either top or bottom of the open digester tank (ODT). The bottom seed sludge transfer process led to better results including a 24 day start-up period, stable pH condition (pH 6.8-7.2), high COD removal efficiency (>90%), satisfactory VFA to Alk ratio (<0.3) and satisfactory biogas production of nearly 1.8 kg m-3 d-1 with methane composition of 50 to 60%. The presence of high amount of methanogens in the seed sludge was able to reduce the long acclimatization period and the CDT could be fed with POME within less than a day after the transfer process was completed. Scanning electron microscopy (SEM) and fluorescence in situ hybridization (FISH) pictures revealed abundant amounts of bacteria and methanogens, in particular Methanosaeta sp. in the seed sludge samples which are very important for the biomethanation process. In chapter 5, the effect of higher sludge recycling rate was studied by applying organic loading rates (OLR) (between 1.0 and 10.0 kgCOD m-3 d-1) at different sludge recycling rates (6 m3 d-1, 12 m3 d-1 and 18 m3 d-1). At sludge recycling rate of 18 m3 d-1, the maximum OLR achieved was 10.0 kgCOD m-3 d-1 with biogas and methane productivity of 1.5 m3 m-3 d-1 and 0.9 m3 m-3 d-1, respectively. By increasing the sludge recycling rate, the VFA concentration accumulated inside the CDT was controlled below its inhibitory limit (1000 mg L-1) and the COD removal efficiency recorded was above 95%. Two methanogens species (Methanosarcina sp. and Methanosaeta concilii) have been identified from sludge samples obtained from the digester and recycled stream. By increasing the sludge recycling rate upon treatment at higher OLR, the treatment process was kept stable with high COD removal efficiency. In chapter 6, the effect of mixing was studied by applying four different mixing regimes i.e natural mixing (NM), minimal horizontal mixing (MHM), minimal horizontal and vertical mixing (MHVM) and vigorous mixing (VM) in the CDT. The COD removal efficiency recorded satisfactory result (> 90%) when subjected to the first three mixing regimes but reduced to the lowest of 85% when VM was applied. In the NM, MHM and MHVM experiments, the maximum VFA concentration in the CDT were recorded below the critical level of 1000 mg L-1. The MHM gave the highest methane productivity at 1.4 m3 m-3 d-1 in comparison to NM at 1.0 m3 m-3 d-1 and MHVM at 1.1 m3 m-3 d-1. This indicates MHM was sufficient for contact between substrate and microorganisms and to release the entrapped biogas inside the CDT. In contrast, VM was found to inhibit the methane production process VFA concentration was recorded high at 3700 mg L-1. The high VFA concentration have disrupted the syntrophic relationship between acidogens and methanogens and inhibited the methanogenesis. In chapter 7, the effect of co-digestion of POME and RGWW under mesophilic condition at different RGWW percentages (1.0-5.25%). The digester performance in terms of COD removal efficiency and methane production rate and stability were evaluated. At 1.0% of RGWW co-digested, both COD removal efficiency and methane production rate showed satisfactory results with higher than 90% and 505 m3 d-1, respectively. However, once the percentage was increased to a maximum of 5.25%, COD removal efficiency remains high but the methane production rate reduced to 307 m3 d-1. At this stage, the digester became unstable due to high VFA concentration of 913 mg L-1 and low cells concentration of 8.58 g L-1 inside the digester. This was due to the effect of plasmolysis on the methanogens at high NaCl concentration. Thus co-digesting of RGWW with high NaCl content and POME is satisfactory for COD removal but not for increasing the methane production